Kebijakan Pedoman Pemidanaan Terhadap Pelaku Tindak Pidana Korupsi - Yasmirah Mandasari Saragih; Ariansyah Ariansyah (Universitas Mataram, 2022)
The crime of corruption that occurred in Indonesia is very widespread and has an impact that is felt in all people's lives. Its development continues to increase from year to year, in the number of cases that continue to become cases with total state financial losses and in terms of the quality of corruption that is carried out systematically. An increase in criminal acts of corruption that will not control the impact that is not only limited to the life of the national economy but also to the life of the nation and state in general. This study uses a normative juridical approach. Normative research is carried out on theoretical matters as laws relating to law enforcement in criminal acts of corruption in Indonesia. With the Supreme Court Regulation Number 1 of 2020 concerning Guidelines for the Criminalization of Articles 2 and 3 of the Corruption Eradication Law, it is hoped that it will become a guideline in the context of imposing criminal penalties on perpetrators of corruption so that the punishment applied can guarantee legal certainty and approach a sense of justice in efforts to provide a deterrent effect